PENGGUNAAN MEDIA TIKTOK DALAM MENINGKATAN HASIL BELAJAR IPA DI MTSN 4 GUNUNGKIDUL - GIARTI SUPRIHATIN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This Classroom Action Research uses Tiktok Media in the learning process which aims to improve science learning outcomes for class VIIIE students. The Covid-19 pandemic has affected children's learning process from offline to online. The increasing use of media affects learning outcomes. This study uses observation to determine the learning process using Tiktok media, and evaluation tests to determine student learning outcomes. The research results obtained are: (1) The process of using Tiktok media in learning is as follows: 1: motivation; 2: delivery of materials; 3: evaluation. (2) The increase in science learning outcomes for class VIIIE MTsN 4 Gunungkidul students can be seen in the percentage of students in the Unfinished Condition Initial which is less than the KKM 50%, which drops to 38% in the first cycle and then decreases to 25% in the second cycle. Students' Completeness Score is the same as the KKM of 38%, increasing to 46% in the first cycle and then increasing to 53% in the second cycle. The Complete Exceeding KKM 12% increased to 16% in the first cycle and then increased to 22% in the second cycle. ABSTRAKPenelitian Tindakan Kelas ini menggunakan Media Tiktok dalam proses pembelajaran yang bertujuan untuk meningkatkan hasil belajar IPA pada peserta didik klas VIIIE . Pandemi Covid-19 mempengaruhi proses belajar anak dari luring (offline ) ke daring (online). Meningkatnya penggunaan media mempengaruhi hasil belajar. Penelitian ini menggunakan observasi untuk mengetahui proses pembelajaran menggunakan media Tiktok, dan tes evaluasi untuk mengetahui hasil belajar pserta didik. Hasil penelitian yang didapat adalah: (1) Proses penggunaan media Tiktok dalam pembelajaran sebagai berikut: 1: motivasi; 2: penyampaian materi; 3: evaluasi. (2) Peningkatan hasil belajar IPA pada peserta didik klas VIIIE MTsN 4 Gunungkidul terlihat pada prosentase peserta didik pada Kondisi yang belum tuntas Awal yang kurang dari KKM 50 % turun menjadi 38% pada siklus I kemudian turun menjadi 25 % pada siklus II. Nilai Tuntas Peserta didik sama dengan KKM 38% naik menjadi 46% pada siklus I kemudian naik menjadi 53% pada siklus II. Nilai Tuntas Melampaui KKM 12% naik menjadi 16 % pada siklus I kemudian naik 22% pada siklus II.